1996
DOI: 10.1002/(sici)1098-0997(1996)4:3<152::aid-idog9>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Immune recognition of the 60kD heat shock protein: Implications for subsequent fertility

Abstract: The 60kD heat shock protein (hsp60) is a highly conserved protein and a dominant antigen of most pathogenic bacteria. In some women, chronic or repeated upper genital tract infections with Chlamydia trachomatis, and possibly with other microorganisms, induces immune sensitization to epitopes of hsp60 that are present in both the microbial and human hsp60. Once a woman becomes sensitized to these conserved epitopes, any subsequent induction of human or bacterial hsp60 expression will reactivate hsp60‐sensitized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
29
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 0 publications
5
29
0
3
Order By: Relevance
“…Cross-reactive anti-heat-shock-protein antibodies and T cells can damage vascular tissues overexpressing heat shock proteins, contributing to the development of atherosclerosis (Mandal et al 2004). Additionally, immune sensitization to human Hsp60, possibly developed as a consequence of infection, may adversely affect pregnancy outcome (Witkin et al 1994(Witkin et al , 1996. Furthermore, the presence of anti-Hsp60 and anti-Hsp70 antibodies in the serum and formation of Hsp60-and Hsp70-immune complexes in the placenta were associated with preterm birth (Ziegert et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-reactive anti-heat-shock-protein antibodies and T cells can damage vascular tissues overexpressing heat shock proteins, contributing to the development of atherosclerosis (Mandal et al 2004). Additionally, immune sensitization to human Hsp60, possibly developed as a consequence of infection, may adversely affect pregnancy outcome (Witkin et al 1994(Witkin et al , 1996. Furthermore, the presence of anti-Hsp60 and anti-Hsp70 antibodies in the serum and formation of Hsp60-and Hsp70-immune complexes in the placenta were associated with preterm birth (Ziegert et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…36 In addition, it could be demonstrated that systemic immunity to human hsp60 was associated with firsttrimester spontaneous abortion. 37 In many IVF culture systems, the in vitro fertilized embryos are cultured in medium containing maternal serum. Preexisting hsp antibodies in these sera at high titers could thus compromise the growth potential of developing embryos.…”
mentioning
confidence: 99%
“…1994). Even a high spontaneous abortion at first trimester during the pregnancy was also found in antibody‐positive women (Witkin et al. 1996).…”
Section: Discussionmentioning
confidence: 92%
“…Improving pregnancy rate during in vitro fertilization (IVF) sometime remains a challenge task. An increased failure rate in women undergoing IVF was found when local and systemic immunity to the human Hsp60 was demonstrated (Witkin et al. 1996).…”
Section: Discussionmentioning
confidence: 99%